Transformations of self: a phenomenological investigation into the lived experience of survivors of critical illness - Papathanassoglou, Elizabeth; Patiraki, Elisabeth (My University, 2003)
Based on the hermeneutical, phenomenological perspective, this study explored the lived experience of individuals with a past hospitalization in an intensive care unit, with focus on their dreams. The purpose was to explore how it is to have been critically ill. Dreams are the language of the unconscious and can symbolically convey meanings. Eight participants recounted their experiences with critical illness through semi-structured phenomenological interviews and dream-telling. An interplay between the 'factual-external' world and the 'internal' world appeared to be the basis of their perception of the situation. Participants' narratives were immensely rich in symbols of transformation, transcendence and rebirth. Transformations in perception, in lived-body, and in lived time and space were some of the themes emerging as part of both conscious and dreaming experiences. Attitudes towards death were altered, and elements of heightened spirituality were evident in the aftermath of critical illness. Critical illness was conceptualized as a 'cocooning phase' leading to transformation of self, spiritual arousal and personal growth. Nurses may be able to alleviate suffering by supporting this process while in the ICU, as well as after discharge
Keywords: Critical care nursing; Catastrophic illness; Attitude to death; Intensive care units; Life change events; Nursing; Research